2020
DOI: 10.12659/msm.928755
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on the Effects of Convalescent Plasma Therapy in 24 Patients Diagnosed with COVID-19 Pneumonia in February and March 2020 at 2 Centers in Wuhan, China

Abstract: Background This retrospective study aimed to describe the effects of convalescent plasma therapy in 24 patients diagnosed with coronavirus disease 2019 (COVID-19) pneumonia due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection during February and March 2020 in Wuhan, China. Materia/Methods The confirmation of SARS-CoV-2 infection was made by the reverse transcription-polymerase chain reaction test. We retrospectively analyzed the clinical data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Similarly, in a prospective cohort study conducted by Salazar and colleagues in 25 patients with severe or life-threatening COVID-19 [ 17 ], a marked reduction of CRP was observed at days 7 and 14 post-CCP transfusions. These results were replicated in other clinical trials [ 18 , 19 , 20 ]. Other studies compared the cytokine profile of CCP with that in plasma from healthy blood donors and found higher levels of IL-10, a potent anti-inflammatory cytokine, and IL-21, which is involved in plasma cell generation and antiviral immune responses [ 21 ].…”
Section: Potential Beneficial Factors In Ccpsupporting
confidence: 68%
“…Similarly, in a prospective cohort study conducted by Salazar and colleagues in 25 patients with severe or life-threatening COVID-19 [ 17 ], a marked reduction of CRP was observed at days 7 and 14 post-CCP transfusions. These results were replicated in other clinical trials [ 18 , 19 , 20 ]. Other studies compared the cytokine profile of CCP with that in plasma from healthy blood donors and found higher levels of IL-10, a potent anti-inflammatory cytokine, and IL-21, which is involved in plasma cell generation and antiviral immune responses [ 21 ].…”
Section: Potential Beneficial Factors In Ccpsupporting
confidence: 68%
“…Though large-scale studies have concluded that COVID-19 CP is generally safe for patient use, 40 proof of its effectiveness in improving outcomes has been equivocal. 39 , 49 , 70 , 80 With the rising use of antiviral drugs such as Remdesivir, the use of CP has fallen out of favor for management of COVID-19, but it is still of use in the study of potential long-term vascular complications of SARS-CoV-2.…”
Section: Blood Supply: Current Statusmentioning
confidence: 99%
“…Furthermore, in early studies, convalescent plasma transfusion showed an effective clinical outcome for patients with severe and critical symptoms. Whereas the preliminary data were promising, a retrospective study calculated that the effective rate was below 60% [ 134 , 135 ]. In a survey of 16,287 UK hospitalized patients, the convalescent plasma treatment made no significant improvement in the survival of patients who received the treatment compared to those who did not [ 136 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%